Analysing the efficacy of polidocanol in injection snoreplasty - K., Manjunath; Singh, Amardeep; S. V., Manjunatha Rao; S., Akash Aradhya (International Journal of Otorhinolaryngology and Head and Neck Surgery, 2020)
Background: Injection snoreplasty was recently introduced as a safe, effective, and minimally invasive treatment for primary snoring. The objective of the study was to assess the effectiveness of the treatment in our patients. Methods: The study was a prospective, non-randomised study done on 40 patients with primary snoring. Study was done in the Department of Otorhinolaryngology and Head and Neck Surgery at Basaveshwara Medical College and Hospital, Chitradurga over 8 months between March 2019 to October 2019. The data was collected from patients about their symptoms. Detailed clinical and radiological examination was done in all patients. Almost each and every causes of snoring were ruled out. 1-3% polidocanol injection of about 1 ml with insulin syringe was administered in all the patients in 1 to 3 sittings after 10% LOX spray application on the site. Patients were assessed after 1, 3 and 6 months and their improvement was noted. Results: There were 24 (60%) males and 16 (40%) females enrolled in our study with mean age as 42±5 years. The average BMI of patients was 27.14±3.1 kg/m2. All the patients except 4 were initially injected 1% polidocanol injection; the others were injected 3%. 4 (10%) patients were re-injected at 1 month and 4 (10%) had 2nd re-injection at 3 months follow up. The mean improvement in symptoms was 58%. Eleven patients (27.5%) had moderate snoring while the rest had severe snoring. The only side effect was pain which in majority of patients was mild. There was no correlation between BMI and percentage of improvement. Conclusions: Injection snoreplasty is a safe and cost-effective treatment for primary snoring.